2018
DOI: 10.1021/acsami.8b00942
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conductive Metal–Organic Framework for a High-Performance Lithium–Sulfur Battery Host: 2D Cu-Benzenehexathial (BHT)

Abstract: Despite the high theoretical capacity of lithium-sulfur (Li-S) batteries, their commercialization is severely hindered by low cycle stability and low efficiency, stemming from the dissolution and diffusion of lithium polysulfides (LiPSs) in the electrolyte. In this study, we propose a novel two-dimensional conductive metal-organic framework, namely, Cu-benzenehexathial (BHT), as a promising sulfur host material for high-performance Li-S batteries. The conductivity of Cu-BHT eliminates the insulating nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 63 publications
2
111
0
Order By: Relevance
“…54,67 The monolayer of Cu-BHT MOF has intrinsic metallic nature mainly contributed from the electronic states of C 2p, S 3p, and Cu 3d orbitals at the Fermi level and is dynamically 8 stable. 68 This metallic characteristic of Cu-BHT MOF could be quite beneficial in improving the rate performance of Al-S battery. The graphene monolayer optimized for the comparative study is also shown in Figure 1c with the lattice parameters (a = b = 2.46 Å) in good accordance with the experimental data for graphite.…”
Section: Computational Detailsmentioning
confidence: 98%
“…54,67 The monolayer of Cu-BHT MOF has intrinsic metallic nature mainly contributed from the electronic states of C 2p, S 3p, and Cu 3d orbitals at the Fermi level and is dynamically 8 stable. 68 This metallic characteristic of Cu-BHT MOF could be quite beneficial in improving the rate performance of Al-S battery. The graphene monolayer optimized for the comparative study is also shown in Figure 1c with the lattice parameters (a = b = 2.46 Å) in good accordance with the experimental data for graphite.…”
Section: Computational Detailsmentioning
confidence: 98%
“…As mentioned in Section 2.1.4, some of conductive MOFs have been reported such as 2D conjugated conductive MOFs. Very recently, such 2D conductive MOFs indeed have been used in Li−S batteries and proven to be promising host materials for S and polysulfides, paving the way for high‐performance Li−S batteries . For example, Li et al .…”
Section: Mofs For Lithium‐sulfur Batteriesmentioning
confidence: 99%
“…Very recently, such 2D conductive MOFs indeed have been used in Li−S batteries and proven to be promising host materials for S and polysulfides, paving the way for high‐performance Li−S batteries . For example, Li et al . demonstrated the promising application of 2D conductive Cu‐BHT as a host for S using a theoretical approach.…”
Section: Mofs For Lithium‐sulfur Batteriesmentioning
confidence: 99%
“…However, only very few MOFs exhibit intrinsic electrical conductivity. The rare examples rely on the formation of p-stacked pathways through threedimensional MOFs, 30,31 delocalization in two-dimensional coordination polymers [32][33][34][35][36] or via sulfur-based linker molecules 37 as well as the special properties of iron-based MOFs. [38][39][40] Alternatively, the introduction of guest molecules like tetracyanoquinododimethane, 41 fullerene, 42 polyaniline and polythiophene derivatives, 40,[43][44][45][46][47][48][49] as well as the formation of composites with conducting carbon modifications 42,[50][51][52][53][54] or conducting polymers 55,56 can lead to conductive MOF-based materials.…”
mentioning
confidence: 99%